Factors influencing public procurement during disasters: the cases of Chile and New Zealand. Issue 2 (18th June 2021) - Aparicio-Arias, Raúl; Moreno, Jenny
Abstract : Purpose: This paper aims to explore public procurement frameworks during disasters in Chile and New Zealand, identifying the factors that affect government procurement performance in disaster response. Design/methodology/approach: This research adopted a case study methodology following a qualitative approach. Semi-structured interviews were conducted with government officers from Chile and New Zealand who had practice-relevant knowledge of public procurement and disaster management. Data was complemented by document reviews, including government reports and the records of disaster management organizations. Findings: This paper finds public procurement to be negatively affected by several factors during disasters, including celerity and flexibility of response; market and supplier restrictions; pressures over procurement teams; centralism of procurement structures; lack of technical knowledge; competition and crossover of agreements; corruption; and price variations. Practical implications: This paper includes policy recommendations on how to increase the effectiveness of disaster management and public procurement systems in countries at high risk of earthquakes and other disasters. Social implications: This paper can help public procurement officers to provide a better response during disasters, supplying the goods and services required to the affected population in a timely and effective manner. Originality/value: This paper addresses a gap in research by identifying factors which negatively impact government procurement and response during a disaster.